The Effect of Polypropylene and Low-Density Polyethylene Mixtures in the Pyrolysis Process on the Quantity and Quality of the Oil Products - Suhendi, Endang; Heriyanto, Heri; Ammar, Muhammad; Tsania, Ayu; Anam, Muhammad Khairul (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2023)
Plastic waste is a type of waste that has economic value when processed properly, one of which is by converting it into fuel oil using the pyrolysis method. Pyrolysis of plastic waste involves the decomposition of materials at high temperatures without the presence of oxygen. This study aimed to examine the effect of the mixture of polypropylene (PP) plastic waste and low-density polyethylene (LDPE) plastic waste in the pyrolysis process on the quantity and quality of the oil products. The ratio of PP:LDPE was varied to 100 kg : 0 kg, 70 kg : 30 kg, 50 kg : 50 kg, and 30 kg : 70 kg. The pyrolysis was conducted at a temperature of 350ºC for 10 hours. The research results show that the highest yield value of 82.24% wt. is obtained at PP:LDPE ratio of 100 kg : 0 kg. Furthermore, the best pyrolysis oil products are obtained at PP:LDPE ratio of 70 kg : 30 kg. The gasoline, kerosene, and diesel fuel products have densities of 760 kg/m3, 776.4 kg/m3, and 873 kg/m3, respectively. Then, the gasoline and diesel fuel have calorific values of 10,836 cal/g and 10,996.5 cal/g. The cetane number of diesel fuel is 42, while the octane number of gasoline is 78.9.